Structural and functional model of involving preschool children to hockey activities - Istomin, S. O.; Naboychenko, E. S.; Kachalov, D. V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the effectiveness of the implementation of the structural-functional model of introducing children aged 5-7 years to hockey.